Netiquette and social media engagement of doctors: A renaissance in health-care delivery - Madhavi Gajula; Bhanupriya S Pande; Bhuvana Gajula; Shwetha Hariba (Asian Journal of Medical Sciences, 2024)
Background: Netiquette is the term used for online etiquette or Internet etiquette. It refers to a set of guidelines, acceptable for communication. With the advent of the pandemic and online taking the major stage for discharging the majority of professional duties, proper netiquette practices among professionals are the basic necessity. Aims and Objectives: The aims and objectives of the study are to assess the knowledge regarding netiquette and its practices among health-care professionals (HCPs) and to determine the factors associated with social media engagement among doctors. Materials and Methods: A cross-sectional observational study was conducted for 2 months, consisting of a total of 64 participants. A pre-tested, semi-structured questionnaire was used to collect data on netiquette and its practices, the professional involvement of health-care personnel in delivering health care, and their encounter with online trolls and harassment. Results: On analysis, it was found that 74.3% had knowledge about netiquette and its practices, however, very few had knowledge about cyberspace usage. Around 68.3% of the participants were unaware of the American Medical Association social media policy for HCPs, guiding the Internet usage for discharging their professional duties. Only 29.7% observed proper netiquette practices to avoid being cyber-bullied. Very few of the study participants faced online troll and harassment and they chose to reply to troll by facts rather than staying quiet. An in-depth study can be done by creating an awareness program as an intervention. Conclusion: Netiquette and its practices are the key to online consultations and practices among HCPs. There is a need to create awareness among them by conducting workshops on the same.